In Vitro and In Vivo Antifungal Activity of Sorbicillinoids Produced by Trichoderma longibrachiatum - Men Thi Ngo; Minh Van Nguyen; Jae Woo Han; Myung Soo Park; Hun Kim; Gyung Ja Choi (Journal of Fungi, 2021)
In the search for antifungal agents from marine resources, we recently found that the culture filtrate of Trichoderma longibrachiatum SFC100166 effectively suppressed the development of tomato gray mold, rice blast, and tomato late blight. The culture filtrate was then successively extracted with ethyl acetate and n-butanol to identify the fungicidal metabolites. Consequently, a new compound, spirosorbicillinol D (1), and a new natural compound, 2′,3′-dihydro-epoxysorbicillinol (2), together with 11 known compounds (3–13), were obtained from the solvent extracts. The chemical structures were determined by spectroscopic analyses and comparison with literature values. The results of the in vitro antifungal assay showed that of the tested fungal pathogens, Phytophthora infestans was the fungus most sensitive to the isolated compounds, with MIC values ranging from 6.3 to 400 µg/mL, except for trichotetronine (9) and trichodimerol (10). When tomato plants were treated with the representative compounds (4, 6, 7, and 11), bisvertinolone (6) strongly reduced the development of tomato late blight disease compared to the untreated control. Taken together, our results revealed that the culture filtrate of T. longibrachiatum SFC100166 and its metabolites could be useful sources for the development of new natural agents to control late blight caused by P. infestans.